The effect of vitamin D on cognitive functions in young female patients: a prospective controlled study using the Montreal Cognitive Assessment - Ozlem Balbaloglu; Nermin Tanık (Arquivos de Neuro-Psiquiatria)
ABSTRACT Aim: Our aim was to determine whether there is a relationship between vitamin D [25(OH)D] and cognitive functioning in women with low 25(OH)D levels. Methods: Ninety female patients, 25-45 years of age, who attended our outpatient clinic and had 25(OH)D levels < 30 ng/mL, were included. The Montreal Cognitive Assessment (MoCA) scale was used to determine cognitive functioning; the scale is divided into seven subgroups. Patients were divided into three subgroups according to their 25(OH)D levels. After a three-month period of 25(OH) D replacement, the patients underwent a re-evaluation using the MoCA scale. Results: The total MoCA score before treatment was significantly different from the score after treatment (p < 0.05). Language and delayed recall functions were significantly different before and after treatment (p < 0.05). Conclusion: Vitamin D levels were related to cognitive functioning in our study group.